Effect of hydrocolloid on the physicochemical properties of theophylline-loaded agar microspheres - Kotadiya, Rajendra; Patel, Vishnu; Surti, Hemangi; Patel, Harsha (Asian Journal of Pharmaceutics (AJP), 2014)
Theophylline-loaded agar microspheres were prepared and the effect of hydrocolloid on the physicochemical properties of the microspheres was investigated. Microspheres were prepared by the w/o emulsion solvent evaporation technique. Microspheres were spherical and free flowing, with particle size in the range of 105-123 Î¼m. It was found that as the concentrations of the polymer and the hydrocolloid increased, the percentage yield, percentage encapsulation and percentage drug content also increased. An in vitro dissolution study was conducted according to the USP method (USP XXII) using apparatus I for 8 h.The dissolution profile of the developed formulation was compared with the marketed product (Theo SR). The similar results of prepared formulation (t50 = 211.78) and marketed product (t50 = 209.29) suggest sustained release of the drug.